Association between preoperative platelet count and postoperative acute kidney injury of patients undergoing abdominal surgery: a retrospective cohort analysis of the INSPIRE database - Yuhuan Wang; Tian Yuan; Xiaodong Zhang; Xingrui Gong (BMC Anesthesiology)
Abstract Background Acute Kidney Injury (AKI) can lead to detrimental outcomes, including prolonged hospital stays, progression to chronic kidney disease, and even mortality. We aimed to explore the association between preoperative platelet count and postoperative AKI in patients undergoing abdominal surgery. Methods We retrospectively extracted data from the INformative Surgical Patient dataset for Innovative Research Environment database (INSPIRE, 2011 to 2020) for patients who underwent abdominal surgery at Seoul National University Hospital. We used logistic regression analysis and restricted cubic spline analysis to investigate the relationship between preoperative platelet count and the risk of developing AKI after abdominal surgery. Results A total of 7,131 patients who underwent abdominal surgery in the INSPIRE database were included in our study. A significant negative association was observed between preoperative platelet counts and postoperative AKI risk across all models (P for trend < 0.001 in unadjusted and partially adjusted models, 0.002 in fully adjusted model). Multivariable-adjusted restricted cubic spline analysis confirmed a significant inverse relationship between preoperative platelet count and the risk of postoperative AKI. The probability of developing AKI after abdominal surgery increased significantly when preoperative platelet counts were below 220 × 109/L. Conclusions Our findings suggest that lower preoperative platelet counts are associated with an increased risk of postoperative AKI. Consequently, preoperative platelet count may serve as a useful indicator for predicting AKI risk after abdominal surgery.